Gene transfer into established and primary fibroblast cell lines comparison of transfection methods and promoters - Ray, J (BioTechniques, 1992)
The stable transfection of immortalized Rat-1 and rat skin primary fibroblast cell lines by calcium phosphate precipitation, lipofection and electroporation methods have been examined. The lipofection method was found to be better than the other methods in terms of higher transfection efficiency and convenient use. Expression of beta-galactosidase from two different viral promoters showed that the level of transgene expression depends on the promoter strength in a particular cell type. The results presented here show that the transgene expression is extremely variable among different colonies generated from individually transfected cells. Therefore, it is necessary to examine individual colonies of cells for the production of reporter gene to obtain cell lines expressing high amounts of gene products